2008
DOI: 10.3171/jns/2008/109/9/0461
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative subcortical stimulation mapping of language pathways in a consecutive series of 115 patients with Grade II glioma in the left dominant hemisphere

Abstract: These results represent the largest experience with human subcortical language mapping ever reported. The use of intraoperative cortical and subcortical stimulation gives a unique opportunity to perform an accurate and reliable real-time anatomofunctional study of language connectivity. Such knowledge of the individual organization of language networks enables practitioners to optimize the benefit-to-risk ratio of surgery for Grade II glioma within the left dominant hemisphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
326
0
18

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 438 publications
(362 citation statements)
references
References 76 publications
11
326
0
18
Order By: Relevance
“…However, even in cases of maximal resection, the percentage of patients who obtain seizure control has been described as ranging from 65% to 80%. 9,13,16,18 Beyond the oncological benefit of extensive resection, these data suggest that the EOR is a strong predictor of postoperative seizure outcome in insular LGGs patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, even in cases of maximal resection, the percentage of patients who obtain seizure control has been described as ranging from 65% to 80%. 9,13,16,18 Beyond the oncological benefit of extensive resection, these data suggest that the EOR is a strong predictor of postoperative seizure outcome in insular LGGs patients.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, it was previously shown that the AF, which connects the middle and inferior temporal gyri with the precentral gyrus and posterior portion of the inferior and middle frontal gyri, 39 subserved phonological processing-thus generating phonemic disturbances when stimulated. 14,19,33 This fascicle represents the anterior limit of resection for glioma within the SS.…”
Section: Surgical and Functional Considerationsmentioning
confidence: 99%
“…At the subcortical level, axonal mapping detected functional fibers in all patients: semantic paraphasia was generated by the stimulation of the upper part of the cavity in all cases, corresponding to the IFOF; alexia was elicited during the stimulation of the basal part of the cavity in 3 cases, corresponding to the ILF; in between, in the depth of the cavity, visual disorders were induced by stimulating the ORs in 5 cases; and phonemic paraphasia was evoked by stimulating the anterior part of the cav- . Before resection (left), cortical mapping allowed the detection of eloquent areas as follows: ventral premotor cortex that elicited speech arrest when stimulated (10), midpart of superior temporal gyrus that provoked anomia (15) and phonemic paraphasia (11) when stimulated, and posterior part of superior temporal gyrus that elicited semantic paraphasia during stimulation (12)(13)(14). After resection (right), the deep functional boundaries have been identified by subcortical electrical mapping as follows: in the SS, ILF that provoked alexia (46), OR that evoked visual disturbances (phosphenes) (48), and IFOF that generated semantic paraphasia (49); in addition, in the anterior part of the cavity (in front of SS) the AF that induced phonemic paraphasia (47).…”
Section: Intraoperative Brain Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative direct electrostimulation under awake anesthesia is the best technique to locate eloquent domains as well as to distinguish functional area from nonfunctional area. In 2008, Duffau and colleagues, reported the largest experience with cortical and subcortical mapping of gliomas affecting the language area 19 . They performed resection using awake craniotomy and direct electrical stimulation in 115 patients.…”
Section: Functional Mappingmentioning
confidence: 99%